2008
DOI: 10.1038/eye.2008.273
|View full text |Cite
|
Sign up to set email alerts
|

Posterior vitreous detachment following cataract surgery

Abstract: Objective To determine the incidence of posterior vitreous detachment (PVD) in a series of patients who have undergone cataract surgery by phacoemulsification. Design Comparative case series Participants A consecutive series of 149 patients who underwent cataract surgery aged between 50 and 60 years were evaluated in this study. Methods Patients identified as being eligible for this study were recalled for an ophthalmic assessment, which included a dilated retinal examination. Main Outcome Measures The status … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(34 citation statements)
references
References 10 publications
2
29
0
3
Order By: Relevance
“…Therefore, though not statistically significant, the presence of VMA was more common in phakic eyes, which is in accordance with the literature for such patients [33] .…”
Section: Discussionsupporting
confidence: 81%
“…Therefore, though not statistically significant, the presence of VMA was more common in phakic eyes, which is in accordance with the literature for such patients [33] .…”
Section: Discussionsupporting
confidence: 81%
“…The removal of the crystalline lens and its replacement with a thinner IOL implant leaves more space inside the globe for the vitreous to move forward which may induce a detachment from the posterior pole. The study also found that eyes with an axial length of more than 25mm were at increased risk of developing PVD (60). Rhegmatogenous retinal detachment (RRD) is rare but is a serious potential complication of cataract surgery.…”
Section: Posterior Vitreous Detachment and Rhegmatogenous Retinal Detmentioning
confidence: 76%
“…A published study found a prevalence of PVD in 50.8% of eyes that had undergone cataract surgery compared to 20.8% in the fellow unoperated eye (60). The removal of the crystalline lens and its replacement with a thinner IOL implant leaves more space inside the globe for the vitreous to move forward which may induce a detachment from the posterior pole.…”
Section: Posterior Vitreous Detachment and Rhegmatogenous Retinal Detmentioning
confidence: 99%
“…This might be explained – as already discussed above – by the higher rate of PVDs in the pseudophakic eye [8] leading to altered vitreous geometry offering enhanced vitreal moving possibilities. This would also explain the higher risk of RD even years after surgery if a PVD occurred after the operation but not necessarily before.…”
Section: Rhegmatogenous Retinal Detachmentmentioning
confidence: 99%
“…In this context it might be noteworthy that also in uncomplicated cataract surgery the rate of PVD is significantly higher than in phakic eyes. Hilford et al [8] observed a PVD rate of 50.8% in pseudophakic eyes versus 20.8% in phakic eyes. This can be explained by the increase in ‘vitreal space’ in the posterior segment after extracting the voluminous lens and exchanging it by a flat artificial lens.…”
Section: Lesions Of the Vitreolenticular Barriermentioning
confidence: 99%